Polyploidy-associated autophagy promotes larval tracheal histolysis at Drosophila metamorphosis. - Pino-Jiménez, B.; Giannios, P.; Casanova, J. (Autophagy, 2023)
Polyploidy is an extended phenomenon in biology. However, its physiological significance and whether it defines specific cell behaviors is not well understood. Here we study its connection to macroautophagy/autophagy, using the larval respiratory system of Drosophila as a model. This system comprises cells with the same function yet with notably different ploidy status, namely diploid progenitors and their polyploid larval counterparts, the latter destined to die during metamorphosis. We identified an association between polyploidy and autophagy and found that higher endoreplication status correlates with elevated autophagy. Finally, we report that tissue histolysis in the trachea during Drosophila metamorphosis is mediated by autophagy, which triggers the apoptosis of polyploid cells.Abbreviations: APF: after pupa formation; Atg: autophagy related; btl: breathless; CycE: Cyclin E; DT: dorsal trunk; fzr: fizzy-related; L3: larval stage 3; PBS: phosphate-buffered saline; RI: RNAi; Tr: tracheal metamere; yki: yorkie.